2020
DOI: 10.1111/jcmm.15310
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation of CCAAT‐enhancer‐binding protein α inhibits lung differentiation in Bronchopulmonary Dysplasia model rats

Abstract: Bronchopulmonary dysplasia (BPD) is a major cause of mortality and morbidity in premature infants, characterized by alveolar simplification, surfactant deficiency, and respiratory distress. In the present study, we have investigated the functional roles of sumoylated CCAAT/enhancer binding protein alpha (C/EBPα) in the BPD rat model. A significant increase in small ubiquitin‐like modifier 1 (SUMO1) and sumoylated C/EBPα protein levels were observed in BPD rats, and the levels of the sumoylated C/EBPα were asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Paradoxically, however, knockdown of the SUMO1 gene increased pulmonary surfactant proteins, decreased glycogen content, and promoted lung differentiation in BPD models, illustrating silencing of the SUMO1 gene protected against hyperoxia-induced lung injury in rats ( 19 ). Furthermore, SUMO1 and SUMO2/3 expression significantly increased in PBMCs of BPD infants, whereas SIRT1 expression markedly decreased ( 18 ), suggesting that more complex regulatory mechanisms regarding SIRT1 need to be further identified.…”
Section: Sirt1 and Bpdmentioning
confidence: 99%
“…Paradoxically, however, knockdown of the SUMO1 gene increased pulmonary surfactant proteins, decreased glycogen content, and promoted lung differentiation in BPD models, illustrating silencing of the SUMO1 gene protected against hyperoxia-induced lung injury in rats ( 19 ). Furthermore, SUMO1 and SUMO2/3 expression significantly increased in PBMCs of BPD infants, whereas SIRT1 expression markedly decreased ( 18 ), suggesting that more complex regulatory mechanisms regarding SIRT1 need to be further identified.…”
Section: Sirt1 and Bpdmentioning
confidence: 99%
“…To further block SUMO1, resulting in increased expression of C/EBP and SPs. Co-immunoprecipitation assays revealed that SUMOylation is critical in regulating the cross-talk between C/EBP and transforming growth factor (TGF) β2, which is a growth factor that inhibits AT2 cell differentiation during lung maturation(Zhu et al 2020 ). The findings suggest that SUMOylation of C/EBP also act as a regulatory mechanism in BPD.…”
Section: Introductionmentioning
confidence: 99%
“…This transcription factor can inhibit cell proliferation by interacting with other proteins or regulating the chromatin remodeling complex. At the same time, CEBPA is involved in the regulation of hematopoiesis and the terminal differentiation of adipocytes, different epithelial cells, and other types of cells ( 8 , 9 ). CEBPA not only balances cell proliferation and differentiation but also regulates cell metabolism, inhibits the process of the cell cycle, and participates in the mitosis of many cell lines.…”
Section: Introductionmentioning
confidence: 99%